2004
DOI: 10.1359/jbmr.0301254
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocyte-Osteoblast Interaction Revealed in Mice Deficient in Transcription Factors GATA-1 and NF-E2

Abstract: Mice deficient in GATA-1 or NF-E2 have a 200 -300% increase in bone volume and formation parameters. Osteoblasts and osteoclasts generated in vitro from mutant and control animals were similar in number and function. Osteoblast proliferation increased up to 6-fold when cultured with megakaryocytes. A megakaryocyte-osteoblast interaction plays a role in the increased bone formation in these mice.Introduction: GATA-1 and NF-E2 are transcription factors required for the differentiation of megakaryocytes. Mice def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
205
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(223 citation statements)
references
References 61 publications
17
205
1
Order By: Relevance
“…Two are targeted genetic deletions of transcription factors, either GATA-1 or NF-E2, both critical to the hematopoietic lineage. 16,38 The third is the overexpression of thrombopoietin leading to a myelofibrotic and osteosclerotic phenotype. 39 Unlike the global effects that are often associated with the loss of a transcription factor, the Pt-vWD mouse is the result of a gain-of-function mutation, by a single amino acid substitution in a single gene product.…”
Section: Discussionmentioning
confidence: 99%
“…Two are targeted genetic deletions of transcription factors, either GATA-1 or NF-E2, both critical to the hematopoietic lineage. 16,38 The third is the overexpression of thrombopoietin leading to a myelofibrotic and osteosclerotic phenotype. 39 Unlike the global effects that are often associated with the loss of a transcription factor, the Pt-vWD mouse is the result of a gain-of-function mutation, by a single amino acid substitution in a single gene product.…”
Section: Discussionmentioning
confidence: 99%
“…Megakaryocytes from Gata1 low mice and from PMF patients express, however, the same intrinsic abnormalities (i.e. higher frequency and higher retention in the marrow because of maturation retardation [6][7][8]56 and increased localization near the endosteum, in close spatial relationship with the osteoblasts 57 . All these factors can contribute to the increased megakaryocyte up-take of SDF-1.…”
Section: Discussionmentioning
confidence: 99%
“…MKs are responsible for the production of thrombocytes, which are necessary for blood clotting. Although the mechanism has yet to be fully elucidated, a growing body of evidence also suggests that MKs play a key role in regulating skeletal homeostasis through direct and indirect effects on OBs and osteoclasts (1)(2)(3)(4)(5)(6). We previously reported that OB cell number is significantly increased when OBs are co-cultured with MKs in vitro (1,2,4).…”
mentioning
confidence: 99%